Two Greek Military Writters in Aelianus Tacitus: Eupolemus of Hypata and Euangelus of Tangara - Sekunda, Nicolas Victor (Polskie Towarzystwo Filologiczne i Uniwersytet Wrocławski, 2019)
The first chapter of Aelian’s Tactics contains a list, which seems to be in roughly chronological order, of previous writers on the military art. Following Alexander II of Epirus (272–c.240 BC) and coming before Polybius (200–118 BC), Aelian lists Clearchus, Pausanias and Euangelus. Later in the same list after Polybius but before Poseidonius the Stoic (135–51 BC) come Eupolemus and Iphicrates. This paper attempts firstly, to identify Euangelus with Euangelus of Tanagra, archōn of the Boeotian League c. 240–225 BC. Secondly, it attempts to identify Eupolemus with Eupolemus of Hypata, who held the post of stratēgos of the Aetolian League in 176/175 BC, fought at Cynoscephalae in 197 BC and was possibly the eyewitness source of information for Polybius on that battle. Other possible identifications of authors in Aelian’s list are then discussed.
Keywords: Tacitus; Eupolemus of Hypata; Euangelus of Tangara